Life Cycle Assessment, Is it Beneficial for Environmental Sustainability? A Literature Review - Bayu Kusuma Adi; Tri Joko; Onny Setiani (Jurnal Serambi Engineering, 2022)
LCA is a method for evaluating the potential environmental effect of a product or service system at all stages of its life cycle by quantifying resource usage and emissions connected with the system under consideration. This paper intends to give an overview of the numerous Life Cycle Assessment (LCA) studies that have been implemented in Indonesian industries in order to reduce the negative effects of pollution on the environment, low distribution, and energy and raw material conservation. In the Life Cycle Assessment (LCA), there are four system boundaries: (cradle to grave), (cradle to gate), (gate to grave), and (gate to grave) (Gate to gate). The scope of this study is restricted to a review of the literature on the application of Life Cycle Assessment from 2018 to 2021, it was published in peer-reviewed journals. There are 11 research publications on the internet with the keywords Life Cycle Assessment (LCA) regarding Life Cycle Assessment (LCA) in Indonesia, which is used to reduce environmental effect in industry. Waste management products, water management, manufacturing industry, mining, fisheries, and plantations are among the research journals covered.